Autoboyography - Lauren, Christina (New York, New York : Simon & Schuster BFYR, 2017)
High school senior Tanner Scott has hidden his bisexuality since his family moved to Utah, but he falls hard for Sebastian, a Mormon mentoring students in a writing seminar Tanner's best friend convinced him to take.
Ages 14 and up.
Keywords: Bisexuality -- Juvenile fiction; Authorship -- Juvenile fiction; Latter Day Saints -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Families -- Utah -- Juvenile fiction; Bisexual teenagers -- Juvenile fiction; Polysexuality -- Juvenile fiction; Sexual orientation -- Juvenile fiction; Utah -- Juvenile fiction; Young adult fiction